2014
DOI: 10.1159/000368422
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Chronic Kidney Disease and Atrial Fibrillation on Morbidity and Mortality in Patients with Acute Myocardial Infarction

Abstract: Background/Aims: Atrial fibrillation (AF) often coexists with acute myocardial infarction (AMI), and chronic kidney disease (CKD) is a major risk for AMI. However, the combined impact of CKD and AF on the mortality and morbidity in AMI population has not been determined. Methods: Between January 2004 and December 2009, a total of 4,738 AMI patients were enrolled prospectively. Patients were divided into four groups according to the combined status of CKD and AF. The primary endpoint was a combination of 5-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
8
0
5
Order By: Relevance
“…Several studies showed that CKD was associated with an increased risk of stroke or systemic thromboembolism amongst patients with AF [5,6,18,19]. Combined CKD and AF were also reported to be associated with an increased risk of mortality in patients with myocardial infarction [20]. A previous study from China including 229 patients with ischaemic stroke (admitted within 1 month of stroke onset) and AF showed that reduced eGFR was independently associated with increased risk of death but not stroke recurrence [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that CKD was associated with an increased risk of stroke or systemic thromboembolism amongst patients with AF [5,6,18,19]. Combined CKD and AF were also reported to be associated with an increased risk of mortality in patients with myocardial infarction [20]. A previous study from China including 229 patients with ischaemic stroke (admitted within 1 month of stroke onset) and AF showed that reduced eGFR was independently associated with increased risk of death but not stroke recurrence [13].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with both AF and CKD there is a 35% increase in relative risk of death 40) and more than a 2-fold increase in major cardiovascular adverse effects. 41) …”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…Characteristics that were repeatedly more common in those who developed NAF included female gender [27, 41, 45, 50, 51]), higher Killip Class [27, 5254], lower LVEF [27, 5054], diabetes mellitus [27, 50, 55], hypertension, [56, 57], and lower renal function [50, 52, 5457]. Parashar et al found that diabetes was less common in those who developed NAF [57].…”
Section: Predicting Those With Acs Who Will Develop Afmentioning
confidence: 99%